From digital museuming to on-site visiting: The mediation of cultural identity and perceived value - Deng, Yuanbing; Zhang, Xinhui; Zhang, Bowen; Zhang, Bei; Qin, Jing (Frontiers in Psychology, 2023)
Introduction Museums use digital resources to provide online services to the public, and a “digital museuming” boom has started. The mechanism of online museum visiting and its impact on willingness to visit on site has become an important issue of widespread concern. Therefore, based on the theory of presence and cognitive-emotional-behavioral theory, this paper introduces perceived value and cultural identity as mediating variables to explore the influence of the digital museuming experience on the willingness to visit on site from the audience’s perspective. Method Questionnaires were distributed, using the snowball sampling method, and 429 valid questionnaires were returned. Results The empirical test presents the following results: (1) virtual reality technology multi-dimensionally expands the digital museuming experience; (2) immersion, interaction and available experience promote willingness to visit on-site; (3) hedonic experience in the process of digital museuming cannot be ignored; and (4) perceived value and cultural identity play a mediating role. Discussion User experience of visiting virtual museums, perceived value and cultural identity influence user willingness to visit museums in the field, but perceived value does not enhance the user’s cultural identity, maybe due to the inability of the online experience to increase the depth of the experience.